Back to the future: the advantage of studying key events in human evolution using a new high resolution radiocarbon method - Talamo, Sahra; Kromer, Bernd; Richards, Michael P.; Wacker, Lukas (PLOS ONE, 2023)
Radiocarbon dating is the most widely applied dating method in archaeology, especially in human evolution studies, where it is used to determine the chronology of key events, such as the replacement of Neanderthals by modern humans in Europe. However, the method does not always provide precise and accurate enough ages to understand the important processes of human evolution. Here we review the newest method developments in radiocarbon dating (‘Radiocarbon 3.0’), which can lead us to much better chronologies and understanding of the major events in recent human evolution. As an example, we apply these new methods to discuss the dating of the important Palaeolithic site of Bacho Kiro (Bulgaria).
Gesehen am 16.10.2023